Camponeses assentados e as práticas agroecológicas no contexto do agrohidronegócio canavieiro no Pontal do Paranapanema (SP) - Rabello, Diógenes [UNESP] (2018)
This Master's Dissertation started from the general objective of understanding the conflicts and impediments imposed by the presence of the sugarcane agroindustrial capital for the agroecological transition in Pontal do Paranapanema (SP). To do this, we used qualitative research using the resources of the semi-structured interview to perform the production of primary information, which together with the bibliographic review on the subject matter and the secondary data, could provide us with arguments and information to discussions on agroecology in Pontal. We are starting from the theoretical understanding that agroecology is a project against model to the model of agriculture created with the Green Revolution, and adopted by the State, which presents us with elements to think about overcoming the monopolization of the land and the maintenance of grilagem and process of commoditization of agriculture, based on monoculture and intensive use of agrochemicals. Sugarcane is gaining more and more space in the Pontal do Paranapanema thanks to the agroindustrial capital, grileiros and State alliance, since there are interests in the three parts to maintain this capitalist form of land exploitation rather than the incentive for reproduction of the peasantry. We conclude our work with the idea that agroecology, at Pontal do Paranapanema, has been thought of as a strategy of resistance on earth and as a way of producing healthy food by thinking of another man / woman-nature relationship.